Comparative Analysis of Criminal Liability for the Crime of Desertion in Ukraine and in the International Legal Order - Huchenko, Kateryna (Проблеми сучасних трансформацій. Серія: право, публічне управління та адміністрування, 2023)
According to the Constitution of Ukraine, the protection of the sovereignty and territorial integrity of Ukraine, ensuring its economic and information security are the most important functions of the state and the business of the entire Ukrainian people. The defence of Ukraine, protection of its sovereignty, territorial integrity and inviolability are entrusted to the Armed Forces of Ukraine. One of the most important issues at the present stage (during the russian-Ukrainian war) of our country's development is the reform of the Armed Forces of Ukraine, transition to a new qualitative and professional level, to an improved legislative framework, which, in turn, requires a review of the current military legislation, the establishment of new military legal norms based on the rich experience of developed and promising modern countries. One of the important methods of scientific knowledge is comparative, which is most often used in criminal law research. Moreover, the use of the comparative legal method is extremely important given our country's aspirations for European integration and full membership in the European Union. Among the fundamental social values protected by criminal law, an important place is occupied by the country's defence capability, which is an important guarantee of the key attributes of the state: unity, sovereignty and independence. Desertion is a criminal offence and is considered by the military to be one of the most serious forms of breach of military duty. Desertion has also proved to be a controversial and emotionally charged socio-political issue. Although in peacetime desertion usually receives little attention, emotions can run high in times of conflict or crisis when a nation relies on its military to ensure peace or even to fight for its survival. This article provides a comprehensive analysis of criminal liability for the criminal offence of desertion under Article 408 of the Criminal Code of Ukraine, taking into account legislative changes that have been made to both the General and Special Parts of the current Criminal Code of Ukraine. The author also provides a comparative analysis of criminal liability for the crime of desertion under the Criminal Code of Ukraine, as well as an analysis of criminal liability for the said crime under the laws of other countries. The author also actively emphasises the unacceptably low number of scientific publications on the legal regulation of desertion as a war crime in Ukraine compared to the imposition of punishment and criminal liability for committing such a crime, especially during martial law.